2010
DOI: 10.1007/s00216-009-3416-2
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination by ultra-performance liquid chromatography–atmospheric pressure chemical ionization time-of-flight mass spectrometry of nitrated and oxygenated PAHs found in air and soot particles

Abstract: An ultra-performance liquid chromatographic-atmospheric pressure chemical ionization time-of-flight mass spectrometric (UPLC-APCIToFMS) method for rapid analysis of twelve nitrated polycyclic aromatic hydrocarbons (NPAHs) and nine oxygenated polycyclic aromatic hydrocarbons (OPAHs) in particle samples has been developed. The extraction step using pressurized liquid extraction was optimized by experimental design methods and the concentrated extracts were analyzed without further clean-up. Matrix effects result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 30 publications
4
24
0
Order By: Relevance
“…Screening experiments showed that to obtain an efficient NPAHs and OPAHs Under the optimal mentioned conditions, the analytes were eluted within 3.0 minutes from the column within a 5.0 minutes total run cycle, which was considerably shorter than the ones reported by Lintelmann et al [32] and Mirivel et al [33].…”
Section: Selection Of Chromatographic Conditionsmentioning
confidence: 77%
“…Screening experiments showed that to obtain an efficient NPAHs and OPAHs Under the optimal mentioned conditions, the analytes were eluted within 3.0 minutes from the column within a 5.0 minutes total run cycle, which was considerably shorter than the ones reported by Lintelmann et al [32] and Mirivel et al [33].…”
Section: Selection Of Chromatographic Conditionsmentioning
confidence: 77%
“…To monitor atmospheric concentrations of PAHQs, methods using LC–MS or LC‐MS/MS were typically accompanied with the ionization of PAHQs using APCI (Delhomme, Millet, & Herckes, ; Jakober, Charles, Kleeman, & Green, ; Lintelmann, Fischer, & Matuschek, ; Mirivel, Riffault, & Galloo, ; O'Connell, Haigh, Wilson, & Anderson, ; Walgraeve et al, ). In HPLC methods, PAHQs were converted to fluorescent derivatives and detected using FL (Kishikawa, Wada, Ohba, Nakashima, & Kuroda, ).…”
Section: Analytical Methods Of Polycyclic Aromatic Hydrocarbons and Nmentioning
confidence: 99%
“…In this regard, the recently published work of Mirivel et al is perhaps the most significant and worthy of the closest scrutiny (Mirivel et al, 2010). As shown in Table 4, when the levels of individual oxygenated-PAHs from diesel soot are compared with other potential sources, including kerosene soot as well as reference PM for urban air, indoor air, and vehicle exhaust, an interesting pattern emerges.…”
Section: Research Trendsmentioning
confidence: 99%
“…Monocyclic and polycyclic quinones, such as those present in diesel exhaust, are generally highly reactive and capable of forming albumin and hemoglobin adducts that are stable for periods of a month to four months, respectively (Granath et al, 1992). Although some polycyclic quinones are too reactive to be absorbed intact through the lungs without first being scavenged by other nucleophilic receptors, diesel exhaust contains several unique quinones, such as 9,10-phenanthroquinone and 2-methyl-9,10-anthraquinone, whose reactivity may be sufficiently low that blood protein adducts may be detected following an exposure (Mirivel et al, 2010). An example of a recent success in this regard is the use of 1,2-naphthoquinone albumin adduct as a biomarker for occupational naphthalene exposure in coke-oven workers (Waidyanatha et al, 2004).…”
Section: Research Trendsmentioning
confidence: 99%